S134 High prevalence of ischaemic heart disease (IHD) in patients meeting clinico-radiological profile for idiopathic pulmonary fibrosis (IPF). (2nd December 2011) - Schomberg, L E E; Draper, A; Vlahos, I; Devaraj, A; Nair, A; Chua, F
Abstract : Introduction: IPF and ischaemic cardiac disease may share pathological similarities including aberrant tissue remodelling. Given their recognised heterogeneity, we hypothesised that patterns of IPF (usual interstitial pneumonia, UIP; non-specific interstitial pneumonia, NSIP; indeterminate UIP-NSIP) may inter-relate differently with the prevalence of IHD and associated co-morbidities. Methods: Ethical approval was obtained to identify all cases of IPF undergoing high-resolution CT between 2003 and 2010. Details of cardiac disease and its management (risk factors, drug treatment, coronary angiography and revascularisation) were included. Consensus radiological diagnoses were reached by 2 chest physicians and 2 thoracic radiologists. Comparison of multiple variables was undertaken using logistic regression (STATA V.11). Results: Of 256 potentially suitable cases, 96 fulfilled ascertainment and were consented: 38 (40%) UIP, 44 (48%) NSIP and 14 (16%) indeterminate (INDET) pattern. An inter-observer k coefficient of 0.56 was calculated for radiological agreement. Regardless of morphological pattern, patients with IPF had a significant cardiovascular risk profile. Where present, IHD predated IPF in the majority of cases, with the highest occurrence (58%) in the UIP subgroup. UIP patients were of comparable age, gender frequency, smoking status and had similar rates of major cardiovascular risk factors as NSIP and INDET subjects. Crucially, they were 2.5 times more likely than NSIP patients to have IHD after adjustment for key determinants of smoking, gender, DM, HTN, hypercholesterolaemia and BMI. On univariate analysis, BMI was significantly higher in the NSIP subgroup (p=0.025 vs UIP or INDET). Rates of STEMI and strokes were highest in UIP cases (n/s) whereas that of CABG was highest in the INDET subgroup. These observations were corrected for IPF severity in so far as FVC and DLCO were decreased comparably across all three radiological subgroups. Evaluation of co-existing COPD was not undertaken; however, mean FEV1 did not differ between groups. Conclusions: Amongst patients with clinical IPF, UIP morphology correlates with the highest risk of cardiovascular morbidity compared to NSIP. A tendency for ischaemic heart disease to precede IPF in the majority of cases suggests the possibility that broader systemic or cardiac-specific factors may influence the pathogenesis of these pulmonary disorders.